Structural Use of Bamboo in Rural Housing - Mishra, Harendra Nath (Indian Forester, 1988)
Because of their suitable strength properties, preferential costs and easy availability even in the hilly and rural areas, bamboo are now being widely favoured by millions of people in house construction. In additlon to the partial solution to the perplexing housiug problems in the country, mass use of structural bamboos can also ease and economise the availability of other constructional materials, like steel, cement, timber etc., in the market. More use of bamboos by more people requires creation of a sense of self confidence in their minds by imparting some basic training in carpentry and or exposing them to some model works so that they can use the necessary techniques and materials to get a comfortable and stable shelter for them. Keeping these points in view, an attempt has been made in this paper to deal with the practical aspects of structural use of bamboo in important components of houses by incorporating the needful techniques developed in the Timber Engineering Branch, F.R.I., Debra Dun.